Volodymyr Zelenskyy, heroic leadership, and the historical gaze. (February 2023) - Spector, Bert
Since the onset of Russia's invasion of Ukraine, a great many people have cojoined their admiration for the grit and determination shown by the Ukraine people with their esteem for the nation's formal leader, Volodymyr Zelenskyy. He has been constructed, particularly in the Western press, as kind of larger-than-life hero, displaying physical courage, resilience, and a brilliant use of communication skills to help mobilize world opinion. But the construction of heroic leadership raises concern within the framework of critical leadership given the often-accompanying characteristics of worshipful acquiescence, hyper-masculinity, and an overly individualized view of causation. In addressing the tension between holding Zelenskyy up as an admirable, even heroic leader while simultaneously harboring a deep distrust of any notion of heroic leadership, the essay examines the historiography devoted to an earlier heroic leader, Martin Luther King, Jr. The goal of this essay is to provoke thought and deepen an appreciation for the complexity of the heroic leadership construct. Graphical Abstract